Νομισματική πολιτική και διανομή του εισοδήματος - Αργείτης Γεώργιος (SPOUDAI Journal of Economics and Business, 1999)
The aim of this paper is to develop a political-monetary perspective, which advances the macroeconomic underpinnings of the effects of monetary policy and the interest rate on income distribution. This perspective finds its roots mainly in the writings of Marx and Sraffa who have attempted to develop some consistent analytical conditions, allowing the establishment of a monetary theory of distribution. At the centre of this perspective are the conflicting economic interests between the industrial sector and the financial sector, and the way that monetary policy and the interest rate affect the intra-capitalist and the interclass income distribution. This perspective establishes an important linkage between intra-capitalist distributional conflicts, monetary policy and income distribution, with significant implications in the field of the politics of monetary policy and the politics of the central bank.